Pengembangan Sistem Manajemen Indekos Griya Indira Terintegrasi WhatsApp Gateway dan Fitur Komunitas - Saputra, Rizki Maulana; Jazuli, Ahmad; Wijayanti, Esti (STMIK Banjarbaru, 2026)
The reliance on manual recording in the operational management of Griya Indira has resulted in data redundancy, a high incidence of late payments, and uneven information distribution among residents. This study proposes the development of an integrated boarding house management system that synergizes the WhatsApp Gateway feature for automatic notifications with a digital community module. Utilizing the Rapid Application Development (RAD) method and Black Box Testing for functional verification, the system is designed to address administrative inefficiencies. The findings indicate that the implementation of Cron Job scheduling successfully transmits bill reminders in real-time and accurately validates digital payments. Based on functional testing results, the system is declared valid in executing centralized database mechanisms, sending automatic bill notifications on schedule, and facilitating single-door information distribution through community features according to design requirements.Keywords: Boarding House Management System; WhatsApp Gateway; Rapid Application Development; Auto-Reminder. AbstrakKetergantungan pada pencatatan manual dalam pengelolaan operasional Griya Indira berdampak pada redundansi data, tingginya insiden keterlambatan pembayaran, serta ketidakmerataan distribusi informasi kepada penghuni. Penelitian ini mengusulkan pengembangan sistem manajemen kos terintegrasi yang menyinergikan fitur WhatsApp Gateway untuk notifikasi otomatis dengan modul komunitas digital. Melalui pendekatan metode Rapid Application Development (RAD) dan verifikasi fungsional Black Box Testing, sistem dirancang untuk menangani inefisiensi administrasi. Temuan penelitian menunjukkan bahwa implementasi penjadwalan Cron Job berhasil mengirimkan pengingat tagihan secara real-time dan memvalidasi pembayaran digital secara akurat. Berdasarkan hasil pengujian fungsional, sistem dinyatakan valid dalam menjalankan mekanisme sentralisasi basis data, pengiriman notifikasi tagihan otomatis sesuai jadwal, serta memfasilitasi distribusi informasi satu pintu melalui fitur komunitas sesuai rancangan kebutuhan.Kata kunci: Sistem Manajemen Indekos; WhatsApp Gateway; Rapid Application Development; Auto-Reminder